Ten Canadian Writers in Context - Coady, Lynn,Chen, Ying,Crummey, Michael,Delisle, Jennifer,Dobson, Kit,Edwards, Caterina,Endicott, Marina,Carrière, Marie J.,Gillespie, Curtis,Purcell, Jason (The University of Alberta Press, 2016)
A superb compilation of modern Canadian voices: ten years, ten authors, ten critics.
Description based on publisher supplied metadata and other sources